On The Stability for Covid-19 Model - Jwan S. Ali; Hero W. Salih (ASJ - Academic Science Journal, 2024)
In this paper, we investigate the stability of an impulsive mathematical model for a biological phenomenon that caused millions of people to die in these recent years, and it is the phenomenon of the COVID-19 epidemic, which first appeared in Wuhan, China. In this study we are working on the system that was proposed by Ndaïrou et al [1] to define the dynamics of COVID-19 model. For the stabilization study we use the direct and indirect Lyapunov method. Before we start a study, we must find all the critical points of the system. For more study, we perturbation the system by adding very small positive quantities, because in finding critical points we have three free variables in case of perturbation, can work on more points. It physically means that we can control a patient’s condition and reduce the number of dead and injured recovering.